Rank, Coclass, and Cohomology. (18th December 2019) - Symonds, Peter
Abstract: We prove that for any prime p the finite p -groups of fixed coclass have only finitely many different mod-p cohomology rings between them. This was conjectured by Carlson; we prove it by first proving a stronger version for groups of fixed rank.